Peningkatan Ekonomi Masyarakat Berbasis Filantropi Islam Di Lembaga Sosial Keagamaan - Faridatun Najiyah; Noor Iffatin Nadhifah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This research illustrates the importance of optimizing ZIS activities based on Islamic philanthropy from the perspective of religious morality. Zakat is not only considered a religious ritual, but also a moral obligation that goes beyond just a formal act. LAZIZMU shows a commitment to managing ZIS funds professionally, with a focus on using funds for productive businesses aimed at improving community welfare. LAZIZMU conducts careful surveys of mustahik to ensure the distribution of funds is on target. Apart from that, LAZIZMU applies a consumptive and productive approach in managing ZIS funds, by providing direct assistance and providing business capital through the BUM program. The selection and mentoring process carried out by LAZIZMU has proven to be effective in empowering mustahik, by providing training and support in developing their businesses. The entire aid distribution process is carried out directly by LAZIZMU to ensure transparency and accuracy in the distribution of funds.